PENGARUH KINERJA ESG DAN KARAKTERISTIK DEWAN TERHADAP KINERJA KEUANGAN (Studi pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Negara-Negara di Asia Tahun 2022-2024) - Naddya Nur Adhani; Surya Raharja (Diponegoro Journal of Accounting, 2026)
Mining companies listed on stock exchanges in Asian countries operate in a sector that is closely associated with environmental exposure, regulatory scrutiny, and growing expectations from stakeholders regarding sustainability and governance practices. In this context, the adoption of Environmental, Social, and Governance (ESG) principles, along with effective board structures, is considered essential in strengthening corporate performance and long-term value creation. This study seeks to investigate empirically the impact of ESG performance and board characteristics—namely board size, board independence, and gender diversity—on the financial performance of mining firms listed on Asian stock exchanges for the 2022–2024 period.This research applies a quantitative research design using secondary data collected from the Refinitiv database and companies’ published financial statements. The sample was determined through purposive sampling based on specific selection criteria. A total of 61 mining companies met the requirements and were observed over three years, resulting in 183 firm-year observations after the removal of outliers. Financial performance is proxied by Return on Assets (ROA). The data are analyzed using multiple linear regression analysis.The empirical findings reveal that ESG performance has a positive and statistically significant relationship with financial performance. Board independence is also found to positively and significantly affect ROA. In contrast, board size and board gender diversity do not demonstrate a significant influence on financial performance. These results imply that sustainability performance and independent oversight play a meaningful role in enhancing profitability, while certain board attributes may not directly translate into short-term financial gains.